2008
DOI: 10.1002/ajp.20645
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters in Guizhou snub‐nosed monkeys (Rhinopithecus brelichi)

Abstract: In this study, we present data on reproductive parameters and birth seasonality of Guizhou snub-nosed monkeys (Rhinopithecus brelichi). Our analyses are based on data from a small captive population collected over 15 years and on 5 years of observations of free-ranging snub-nosed monkeys. Captive females (n=4) mature at an age of 70.8+/-6.7 months and reproduce for the first time at 103.4+/-7.5 months. The mean interbirth interval was 38.2+/-4.4 months if the infant survived more than 6 months, which is longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Lasha exhibited strict birth seasonality, with births occurring from mid-February to early April, and females giving birth every second year. These results were not surprising; earlier studies on R. bieti (Xiang and Sayers 2009), R. roxellana (Zhang et al 2000;Ren et al 2003;Qi et al 2008), and R. brelichi (Yang et al 2009) have shown similar seasonality and annual birth rates within the genus. For primates, especially at the higher latitudes where temperatures and food resources undergo pronounced seasonal fluctuations, most species exhibit seasonality in breeding (Brockman and van Schaik 2005;Janson and Verdolin 2005).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Lasha exhibited strict birth seasonality, with births occurring from mid-February to early April, and females giving birth every second year. These results were not surprising; earlier studies on R. bieti (Xiang and Sayers 2009), R. roxellana (Zhang et al 2000;Ren et al 2003;Qi et al 2008), and R. brelichi (Yang et al 2009) have shown similar seasonality and annual birth rates within the genus. For primates, especially at the higher latitudes where temperatures and food resources undergo pronounced seasonal fluctuations, most species exhibit seasonality in breeding (Brockman and van Schaik 2005;Janson and Verdolin 2005).…”
Section: Discussionsupporting
confidence: 75%
“…As with other species of Rhinopithecus (Zhang et al 2000;Ren et al 2003;Li and Zhao 2007;Qi et al 2008;Yang et al 2009), breeding behavior (copulations) occurred year-round, but peaked between July and October, or 6-7 months prior to the birth season (Xiang and Sayers 2009). In the present study, copulation frequency was closely related to each tested environmental factor at least once within the previous year, indicating several factors may be involved in regulating reproductive function, as well as highlighting the complex inter-connection and inter-dependence between environmental variables.…”
Section: Discussionmentioning
confidence: 92%
“…The clock model was set to a strict clock with a generation time of 12 years according to a female age of first reproduction of 8–9 years, and a lifespan of about 18 years [45]. We used a substitution rate of 0.1643 substitutions per nucleotide per million years [21] and a coalescent Bayesian Skyline tree prior with 10 groups under a piecewise-constant skyline model.…”
Section: Methodsmentioning
confidence: 99%
“…Published, cross‐species compilations served as guides but every data point was taken from the original literature. Recently published data for captive Rhinopithecus brelichi were not included due to a possible effect of inbreeding in the colony leading to a late age at first birth (8.6 years) and a reduced reproductive rate (interbirth interval: 38.2 months; Yang et al, 2009: p 269). We further evaluated these data points by regressing all available data on body mass.…”
Section: Methodsmentioning
confidence: 99%